Kultura gruzińska a europejska — z historii wzajemnych oddziaływań - Furier, Andrzej (Studia Europaea Gnesnensia, 2010)
The article attempts to present selected elements of the complex interactions on the Georgian-European axis since the ancient times to the present day. Georgia’s location at the crossroads of Europe and Asia made western and eastern influences collide there, in all areas of social life—from politics, to material and spiritual culture. The development of Georgian culture has always been closely linked to political developments, and in some sense forced to adapt itself in this field. The first period of encounter between Georgian and European culture took place in ancient times. Mutual contacts were then sporadic in nature and were limited to selected sites, such as Greek factories on the Georgian coast of the Black Sea. In the Middle Ages the number of contacts increased and their nature changed. They reached all corners of Georgia, as well as its rulers, and did not concern trade only. Georgian thinkers participated in the exchange of intellectual property, co-creating philosophy, social and religious thought. What is more, with the unification of Georgian territories by the native dynasty of Bagrationi, the number of political contacts also multiplied. The history of the dynasty is inextricably bound with that of Georgia. They began their rule in the early 9th century, as presiding princes in the historic southwestern Georgia and the adjacent Georgian marchlands reconquered from Arabs. Subsequently, in 888, they restored the Georgian kingdom, which prospered from the 11th to the 13th century, bringing several regional polities under its control. This period of time, particularly the reign of David IV (1089–1125) and his great granddaughter Tamar (1184–1213), is celebrated as a “golden age” in the history of Georgia, the era of imperial grandeur, military exploits, and remarkable achievements in culture. Georgian rulers tried to use contacts with the Crusaders to achieve its political objectives. The reign of David IV and the Battle of Didgori in 1121, discussed in the article, may serve as an example here. After the fragmentation of their unified feudal state in the late 15th century, the branches of the Bagrationi house ruled the three breakaway Georgian kingdoms—Kartli, Kakheti, and Imereti—until the Russian annexation in the early 19th century. In the next period of the Georgian feudal monarchy, the nature of the country’s contacts with Europe underwent another change. This was due to the increased interest in the region from the most powerful states in contemporary Europe—Poland and France. There the Georgians sought allies to fight in Turkey, using Catholic missionaries. Although not able to execute those plans, the journeys of missionaries resulted in many descriptions of the Caucasus, which enriched the knowledge of Europeans of this peripheral region of the continent. A fundamental change in the situation occurred with the acquisition of Georgia through Russia, an intermediary in contacts with Europe. This allowed to eliminate the 19th century pressure of the predatory neighbors from the south. Russification policy the Georgians were subjected to suppressed their own national revival, whose authors were educated in the schools represented by the new elite. Politically, their actions resulted in the 20th century revival of the Georgian state. In all periods of Georgia’s history, western and eastern influences clashed, with the former dominating at first, yet over time the importance of the latter grew. Georgian openness to European cultural models encountered many obstacles that hindered their assimilation. The most important difference here was the custom and traditions, and a pace of development much slower than in Europe. To Georgians, acquisition of western models has a meaning as part of the modernization of their country. Hence the interest in Europe has reached the largest dimensions at the beginning of the 20th century, when Georgian elites had their own state of ore mining. In Europe, there were the then world’s political and economic centers. After World War II, the situation has changed and the United States of America began to display a greater interest in the Georgia. This led to the 1991 Soviet Union’s wider exposure to cultural patterns there. On April 9, 1991, shortly before the collapse of the USSR, Georgia declared independence. On May 26, 1991, Zviad Gamsakhurdia was elected as the first President of independent Georgia. Gamsakhurdia stoked Georgian nationalism and vowed to assert Tbilisi’s authority over regions such as Abkhazia and South Ossetia, which had been classified as autonomous oblasts under the Soviet Union. However, this is a topic for a separate article.